Chaos as a Software Product Line—A platform for improving open hybrid‐cloud systems resiliency. (15th February 2022) - Camacho, Carlos; Cañizares, Pablo C.; Llana, Luis; Núñez, Alberto
Abstract: Nowadays, cloud‐native software architectures have a significant relevance due to the speed and agility they provide. These properties lead relevant organizations in different industries, like video streaming (Netflix), car‐sharing (Uber, Cabify), banking (BBVA, HSBC), and governmental agencies (NASA, FBI, CERN, ESA) to heavily rely on cloud‐native software to run their business‐critical applications. Additionally, including fault injection actions in the production infrastructure allows companies to have consistent environments, to improve applications dependability against unexpected failures, to provide better user experience, and to improve the overall system quality. Thus, cloud computing technologies allow development teams to rapidly create complex systems and to continuously deploy them, at a global scale. This work describes Pystol, a novel fault injection platform—represented as a Software Product Line—to analyze the effects caused by a wide spectrum of adverse conditions. Pystol is designed to be executed on top of cloud‐native environments, either in private or public clouds. The proposed architecture shows a way for representing feature models based on Unified Model Language (in short, UML) component diagrams. Furthermore, we present a thorough empirical study carried out in real‐world environments, providing promising results.